Hail Lifestyle Medicine consensus position statement as a medical specialty: Middle Eastern perspective - Alrajhi, Saleh; Konswa, Ayman Afify; Alhamdi, Nisreen; Alshammari, Farhan; Alqurashi, Alaa; Alraddadi, Rajaa; Alfheeaid, Hani; Albattal, Saad; Alsoqih, Norah; Almuhaileb, Faisal; Alnais, Meshal; Kunonga, Edward; et al. (Frontiers in Public Health, 2025)
Background and importanceLifestyle choices and practices are often the primary contributors to most preventable chronic diseases encountered in both outpatient and inpatient settings worldwide. Lifestyle medicine (LM) therapeutic interventions have consistently been shown through numerous scientific studies to improve and, in many cases, reverse chronic diseases. Globally, there is widespread acceptance of the 15 core competencies, 6 pillars, and the overarching definition of Lifestyle Medicine (LM) established by the American College of Lifestyle Medicine and its partners. While these 6 pillars provide a robust framework, they may not fully address the diverse needs of individuals and populations across various cultures, countries, and communities. The implementation of LM is inherently context-sensitive, influenced by factors such as local legislation, culinary traditions, food availability, economic conditions, agricultural development, whole-food retail accessibility, healthcare infrastructure, training opportunities, community resources, and faith or religious practices at both the individual and community levels. Furthermore, the MENA region, in particular, experiences a disproportionately high prevalence of lifestyle-related non-communicable diseases (NCDs) such as obesity, impaired glucose tolerance (IGT), type 2 diabetes mellitus (T2DM), hypertension (HTN), coronary artery disease (CAD), polycystic ovary syndrome (PCOS), and various forms of cancer, along with other related syndromes and co-morbid conditions. Addressing these challenges requires careful consideration of the local context—a complex interplay of culture, traditions, beliefs, and behaviors—that significantly shapes lifestyle choices, resource availability, and their subsequent impact on health and wellness outcomes. Significantly, the Hail Lifestyle Medicine International Conferences held in 2022 and 2023 have emphasized the strategic importance of Lifestyle Medicine in the MENA region, particularly in Saudi Arabia. These conferences underscored the need to define the scope of practice for Lifestyle Medicine in alignment with the ongoing Saudi healthcare transformation, the region's unique societal features, available local resources, and the specific needs of the population. Furthermore, these conferences served as pivotal platforms for convening experts, facilitating knowledge exchange, and fostering collaborations to tackle the distinct health challenges prevalent in the region. To provide a more comprehensive understanding, information regarding the establishment of the technical working group for the MENA region—critical to conceptualizing and adapting the LM pillars—should be included in the background or methods section earlier in the paper. This addition would offer readers insights into the foundational steps and collaborative efforts that initially shaped the initiative.Establishment of the technical working group for the MENA regionIn response to the rising prevalence of non-communicable diseases (NCDs) and the pressing need for a tailored approach to Lifestyle Medicine (LM) in the MENA region, a Technical Working Group (TWG) was established. The initiative sought to adapt the six pillars of LM to align with the region's unique cultural, economic, and social contexts. The TWG comprised experts from various disciplines, including family medicine, preventive medicine, public health, nutrition, and related fields, ensuring diverse perspectives and expertise in primary care and lifestyle interventions. The concept of adopting expanded LM pillars was initially formulated during a series of international and regional conferences, notably the Hail Lifestyle Medicine International Conferences held in 2022 and 2023. These conferences highlighted the urgent need for a region-specific approach to mitigate the high prevalence of lifestyle-related NCDs in the MENA region. The TWG was tasked with conducting a comprehensive review of the existing LM pillars while taking into account critical factors such as local legislation, culinary traditions, food resources, economic conditions, and health systems infrastructure. To achieve expert consensus on the adapted LM pillars, the Delphi process was employed. This structured communication method involved several rounds of anonymous questionnaires, enabling experts to provide their input and refine their responses based on collective feedback. The process ensured a balanced, inclusive approach that minimized potential power imbalances and produced LM pillars tailored to the MENA region's specific needs.MethodsA survey was distributed to professional group panels representing multiple healthcare specialties, as well as to researchers and healthcare academic leaders of Lifestyle Medicine (LM) across Saudi Arabia and the broader Middle East. A Strength, Weakness, Opportunity, and Threat (SWOT) analysis was conducted, and the Delphi method was employed for structured communication and opinion formation. Using the nominal polling technique, formal responses were collected to develop an official written consensus position statement. The survey questions were validated and approved by an expert panel before being disseminated to the national Lifestyle Medicine group via WhatsApp for voting. Participants were asked to select one of three options: retain the American LM pillars, expand to the newly validated Saudi Arabian (MENA) LM pillars, or abstain from voting (neutral).Conclusions and relevanceOut of 815 members in the national Lifestyle Medicine (LM) group, 136 responses were received, while 679 members abstained from voting, indicating neutrality. Among the 136 votes, 36 supported retaining the LM pillars developed by the American College of Lifestyle Medicine AMCL and its partners without modifications. In contrast, 118 voted in favor of the newly developed MENA/Saudi Arabian pillars, acknowledging the need to address local healthcare needs that extend beyond traditional or classical medicine. The new pillars incorporated motor vehicle driving disturbances as a leading modifiable lifestyle factor contributing to death and disability in the region. Additionally, the impact of smart technology, particularly mobile phones and other devices, was recognized as a key contributor to motor vehicle accidents (MVAs), which significantly increase mortality and disability rates. Further, the new pillars emphasized emotional and mental health, spirituality, and sexuality, driven by the growing demand for comprehensive mental and emotional healthcare combined with faith-based and spiritual empowerment. Finaly, the inclusion of sexuality as a pillar was prompted by rapid societal changes, the rising prevalence of risky sexual behaviors, and the increased incidence of sexually transmitted infections (STIs). These challenges, coupled with the ambiguity surrounding who should manage such patients and the need for timely access to care, highlighted amajor gap in addressing this critical aspect of human health and quality of life. This addition ensures that LM physicians can provide appropriate care to close the gap in services related to sexual health.